EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP NEGERI 1 TANTOM ANGKOLA - Dissa Putri Vera; Yulia Pratiwi Siregar; Nisah Ayu Siregar (JURNAL MathEdu (Mathematic Education Journal), 2018)
The aims of this study is to: 1) describe of using inside outside circle learning model, 2) describe students’ mathematic communication ability before and after using inside outside circle learning model, and 3) describe effectiveness of using inside outside circle learning model on students’ mathematic communication ability at the seventh grade students SMP Negeri 1 Tantom Angkola. This research was conducted by applying experimental method (one group pretest post test design) with sample 30 students and they were taken by using simple random sampling technique. Observation and test were used in collecting the data. Based on descriptive analysis, it was found that: (a) the score of using inside outside circle learning model was 3.9 (very good category), b) the average of students’ mathematic communication ability before using inside outside circle learning model was 33.13 (fair category) and after using inside outside circle learning model was 84.40 (very good category), significant value was 0.00<0.05, and c) N-Gain value was 0.76 (high category), inside outside circle learning model was effective which had percentage 66.7% (effective criteria). It was concluded inside outside circle learning model increased students’ mathematic communication ability at the seventh grade students SMP Negeri 1 Tantom Angkola.